Tuning the phase separated morphology and resulting electrical conductivity of carbon nanotube filled PαMSAN/PMMA blends by compatibilization with a random or block copolymer. (13th January 2017) - Bharati, Avanish; Cardinaels, Ruth; Van der Donck, Tom; Seo, Jin Won; Wübbenhorst, Michael; Moldenaers, Paula
Abstract: The mechanism governing the electrical properties for phase separating blends containing multiwall carbon nanotubes (MWNTs) is unravelled by tuning the compatibilization efficiency. Thereto, compatibilization by interfacially segregated block and random copolymers (cp) of poly(styrene-random/block-methyl methacrylate)(PS-r/b-PMMA) was achieved in phase separating blends of poly[( α -methyl styrene)- co -acrylonitrile]/poly(methylmethacrylate) (P α MSAN/PMMA) undergoing spinodal decomposition. A systematic study of the effects of copolymer architecture and molecular weight on the percolating network of selectively localized MWNTs is performed. Effective compatibilization is achieved with block cp irrespective of the ability of the blocks to entangle, whereas for random cp only long random cp having the ability to effectively entangle with the homopolymers are as efficient as long block cp. With increasing copolymer concentration, an increase and subsequent saturation of the electrical conductivity is attained. This originates from an increased connectivity and refinement of the MWNT laden P α MSAN phase, as confirmed by optical microscopy and the linear viscoelastic response of the blends. An effective compatibilizer led to an interfacial tension mediated suppression of an interfacial coarsening of the P α MSAN phase during phase separation, subsequently leading to percolation of MWNTs selectively localized in the P α MSAN phase. Furthermore, the copolymer having the ability to promote the development of a percolated network of MWNTs also allowed the network to be formed at a lower copolymer concentration as compared to that of blends with copolymers leading to restricted improvement in the connectivity of MWNTs. Our robust and simple procedure to tune the blend morphology via the efficiency of the compatibilizers can be used to achieve a synergistic increase in conducting properties. Graphical abstract: Highlights: Compatibilizers' efficiency in tuning a phase separated blend morphology and the resulting conductivity was studied. Selective localization of MWNTs and compatibilization of phase separating blends by copolymers was the adopted approach. A study of the effects of copolymer architecture and molecular weight (Mw ) was used to tailor the MWNT percolated network. A block copolymer is an effective compatibilizer irrespective of its Mw but a high Mw is required for the random copolymer. A double percolated network of MWNTs resulted in a pronounced increase in the conductivity at low MWNTs concentration.